A certain age - Williams, Beatriz (William Morrow, an imprint of HarperCollins Publishers, 2016)
Falling in love with her paramour but unable to divorce because of societal conventions, married Jazz Age socialite Theresa Marshall tries to make the best of the situation but reconsiders her values when her lover falls for her soon-to-be sister-in-law.